2021
DOI: 10.1186/s13041-021-00729-2
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia risk ZNF804A interacts with its associated proteins to modulate dendritic morphology and synaptic development

Abstract: Schizophrenia (SZ) is a devastating brain disease that affects about 1% of world population. Among the top genetic associations, zinc finger protein 804A (ZNF804A) gene encodes a zinc finger protein, associated with SZ and biolar disorder (BD). Copy number variants (CNVs) of ZNF804A have been observed in patients with autism spectrum disorders (ASDs), anxiety disorder, and BD, suggesting that ZNF804A is a dosage sensitive gene for brain development. However, its molecular functions have not been fully determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Cognitive deficits in many neuropsychiatric disorders are thought to be related to dendritic spines or neurite growth [ 196 , 197 , 198 , 199 ]. In the primary cortical neurons of ZFP804A knockdown rats, the neurite growth and the density of dendritic spines are significantly reduced, and the upregulation and downregulation of ZFP804A significantly damage the dendritic morphology; furthermore, different ZFP804A binding proteins show varying levels of reversal of dendritic and synaptic defects [ 200 ]. A recent study showed that ZFP804A was necessary for NPC proliferation and neuronal migration, and the overexpression of the gene encoding neurogranin (an SZ risk gene and the target of ZFP804A) can offset the migration defect caused by ZFP804A knockdown [ 193 ].…”
Section: Zfp and The Cellular Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive deficits in many neuropsychiatric disorders are thought to be related to dendritic spines or neurite growth [ 196 , 197 , 198 , 199 ]. In the primary cortical neurons of ZFP804A knockdown rats, the neurite growth and the density of dendritic spines are significantly reduced, and the upregulation and downregulation of ZFP804A significantly damage the dendritic morphology; furthermore, different ZFP804A binding proteins show varying levels of reversal of dendritic and synaptic defects [ 200 ]. A recent study showed that ZFP804A was necessary for NPC proliferation and neuronal migration, and the overexpression of the gene encoding neurogranin (an SZ risk gene and the target of ZFP804A) can offset the migration defect caused by ZFP804A knockdown [ 193 ].…”
Section: Zfp and The Cellular Pathwaysmentioning
confidence: 99%
“…Regulate people's language, reading, and cognitive abilities, and participate in the regulation of cognitive impairment-related diseases [193,195,[200][201][202]…”
Section: Zinc Finger Protein 804a (Zfp804a)mentioning
confidence: 99%
“…SNP rs1344704 is located in the second intron of the ZNF804A gene, being the first to show a significant association with increased susceptibility to schizophrenia in a GWAS (O'Donovan et al, 2008 ), which has been consistently replicated in larger subsequent ones (Ripke et al, 2014 ; Steinberg et al, 2011 ; Williams et al, 2011 ), also extending to bipolar disorder, mainly in the context of European populations. ZNF804A is known to be highly expressed in brain tissues, specifically in the cytoplasm, neurites and dendritic spines in the human cortex (with higher density in the cingulate cortex), as well as in various types of mouse neurons (including pyramidal, dopaminergic and glutamatergic ones) (Dong, Mao, Chen, Yoon, & Mao, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ZFP804A (rodent homologue) was found to be enriched in synaptic fractions, and to localise to dendritic spines, where the majority of excitatory synapses occur in the mammalian brain (Deans et al, 2017). Consistent with a role for the encoded zinc finger protein at synapses, knockdown or knockout of Zfp804A resulted in a reduction of dendritic spine density (Deans et al, 2017;Huang et al, 2020), whereas an increase in spine density was observed when the full length or shorter disease-associated isoform of the protein was overexpressed in cortical neurons (Dong et al, 2021;Zhou et al, 2020). Moreover, activity-dependent remodelling of dendritic spines was impaired in cortical neurons with reduced ZNF804A expression levels (Deans et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…A recent interactome study using a yeast two-hybrid assay has indicated that ZNF804A interacts with multiple proteins, including NT5C2 (Zhou et al, 2018). Follow up studies have demonstrated that ZNF804A forms a complex with several predicted interactors to regulate neuronal morphology (Dong et al, 2021). Interestingly, it was noted that NT5C2 is the only potential interacting protein for ZNF804A, encoded by a GWAS-supported gene (Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%